Extracurricular Management Practices and Their Impact on Students’ Life Skills in an Indonesian Madrasah - Mursalim, Nurul Aulyah; Hasbi, Hasbi; Kartini, Kartini (International Journal of Asian Education, 2025)
This study investigates the management of extracurricular activities and their contribution to students’ life skills development at MTs Bua, a rural madrasah in Indonesia. Despite limited resources, the school consistently delivers extracurricular programmes by applying the Planning, Organising, Actuating, and Controlling (POAC) management cycle while integrating Islamic moral values. The study aims to analyse how extracurricular activities are managed, identify the life skills developed, and explore challenges in their implementation. Using a qualitative case study design, data were collected through in-depth interviews with the principal, vice principal for curriculum, and activity coaches, supplemented by document analysis. Data were analysed thematically following Miles and Huberman’s interactive model. Findings indicate that extracurricular management follows a structured cycle adapted to resource constraints through participatory planning, efficient role distribution, and regular monitoring. Scouting, sports, and arts foster a broad range of life skills, such as teamwork, leadership, emotional regulation, creativity, and communication, while embedding Islamic moral guidance. Challenges include limited facilities, financial constraints, inconsistent participation, and varying levels of coach expertise; these are addressed through flexible scheduling, resource-sharing, and leadership commitment. The study offers a hybrid management model that combines competency-based and values-based approaches, demonstrating that the POAC framework can be effectively adapted in rural Islamic school contexts. It also provides a new perspective on sustainability, showing that leadership commitment and adaptive strategies can sustain extracurricular programmes without substantial infrastructure. These findings have practical implications for school leaders, educators, and policy-makers in designing and sustaining extracurricular activities that promote both skill development and character formation.